The Learning Modalities of Senior High School Students in a Vocational and Industrial School and Its Relation to Communication Skills - LAGO, FE (International Journal of Arts, Sciences and Education, 2021)
This descriptive-correlational study aimed to describe the learning modalities of students as well as to investigate their relationship to English communication performance of Grade 11 students of Reina Mercedes Vocational and Industrial School Reina Mercedes, Isabela. There were 219 student-respondents. The Learning Style Survey of the University of Oregon Career Information System and Tests were adapted from IELTS, and some were adapted and modified from English for Academic and Professional Purposes. The study revealed among others that students have diverse learning modalities where visual learning modality is the most dominant. Majority of the students have average performance level in the listening, speaking, viewing, and writing. The study yielded results that show significant relationship between the students’ learning modalities and their performance in English communication. Hence, it is important to note that teachers need use variety of styles to suit the learning modalities of the students.